2012
DOI: 10.1055/s-0031-1301070
|View full text |Cite
|
Sign up to set email alerts
|

Free Flap Scalp Reconstruction in a 91-Year-Old Patient under Local-Regional Anesthesia: Case Report and Review of the Literature

Abstract: In the elderly population with significant medical comorbidities, the safety of general anesthesia is often in question. In the head and neck, where regional and extradural anesthesia are not options, reconstruction of defects requiring free tissue transfer becomes a particular challenge for patients in whom general anesthesia is contraindicated. We present a case of a scalp reconstruction utilizing a latissimus dorsi free flap in a 91-year-old man performed entirely under local and regional anesthesia. Gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 15 publications
0
11
0
1
Order By: Relevance
“…10 Carey et al elegantly demonstrated a tailored method of treating an elderly patient by achieving free tissue transfer using only regional and local anesthesia. 11 However, avoiding general anesthesia is seldom necessary. Chronological age alone should not deter the reconstructive surgeon from operating on complex defects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 Carey et al elegantly demonstrated a tailored method of treating an elderly patient by achieving free tissue transfer using only regional and local anesthesia. 11 However, avoiding general anesthesia is seldom necessary. Chronological age alone should not deter the reconstructive surgeon from operating on complex defects.…”
Section: Discussionmentioning
confidence: 99%
“…19,31,60,61 We advocate for musclesparing adipocutaneous free tissue transfer to prevent longterm atrophy as seen in case 7 with the muscle-only latissimus dorsi (►Figs. [9][10][11]. Nevertheless, historically multiple studies support the latissimus dorsi myocutaneous flap or muscle only with STSG as the workhorse for reconstruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…51 Free flap operations under epidural anesthesia alone have been reported in cases where general anesthesia was contraindicated. 52,53 Several clinical studies have also demonstrated that peripheral nerve blocks reduce vasospasm and improve perfusion of replanted or revascularized digits. 20,21,54,55 …”
Section: Anesthetic Agentsmentioning
confidence: 99%
“…In some patients, the method of reconstruction may be limited by general health factors precluding general anesthesia, and even a microvascular reconstruction with a latissimus dorsi free flap has been preformed under locoregional anesthesia. 29 In spite of this, not all patients will survive complex surgical treatments and more simple reconstructive options will always be needed. The SP-LD offers many qualities required in these situations.…”
Section: Discussionmentioning
confidence: 99%